2011
DOI: 10.1007/s11049-011-9131-7
|View full text |Cite
|
Sign up to set email alerts
|

Japanese loanword devoicing revisited: a rating study

Abstract: In Japanese loanword phonology, geminates optionally devoice when there is another voiced obstruent within the same stem, i.e., geminates may optionally devoice when they violate OCP(voice). This devoicing of OCP-violating geminates has received much attention in the recent phonological literature. However, the debates centering around this phenomenon have relied primarily on intuition-based data, and no systematic wellformedness judgment experiments have been performed. This paper fills that gap. The experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
21
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 49 publications
9
21
0
Order By: Relevance
“…The experiment indeed showed that Japanese speakers generally judge devoicing of OCP-violating geminates as more natural than devoicing of non-OCP-violating geminates or devoicing of OCP-violating singletons. In this regard, Kawahara (2011b) succeeded in supporting the empirical basis of the claims made about the patterns in (1)-(3). Kawahara (2011a) reports a follow-up experiment using a larger set of stimuli with 49 naive native speakers, which again supported the idea that devoicing of OCP-violating geminates is the most natural environment for native speakers of Japanese.…”
Section: The Phenomenonmentioning
confidence: 79%
See 4 more Smart Citations
“…The experiment indeed showed that Japanese speakers generally judge devoicing of OCP-violating geminates as more natural than devoicing of non-OCP-violating geminates or devoicing of OCP-violating singletons. In this regard, Kawahara (2011b) succeeded in supporting the empirical basis of the claims made about the patterns in (1)-(3). Kawahara (2011a) reports a follow-up experiment using a larger set of stimuli with 49 naive native speakers, which again supported the idea that devoicing of OCP-violating geminates is the most natural environment for native speakers of Japanese.…”
Section: The Phenomenonmentioning
confidence: 79%
“…However, Kawahara (2011b) raises one issue: the Japanese loanword devoicing data are primarily based on the intuitions of two linguists, namely, Nishimura (2003) and Kawahara (2006); i.e. the grammaticality judgments in (1)-(3) primarily come from the authors themselves.…”
Section: The Phenomenonmentioning
confidence: 99%
See 3 more Smart Citations